A testbed for device free indoor localization system - Pirzada, N. (Institute of Electrical and Electronics Engineers Inc., 2016)
Based on wireless sensor networks, device-free indoor localization technique has received much attenuation in the field of indoor localization systems. Due to different indoor environmental parameters, multi-path fading, human presences and different system configurations, the WiFi-based received signal strength indicator (RSSI) values are effected. This paper elaborates on the development of a wireless network test-bed to measure the Received Signal Strength Indicator (RSSI) in different environments, as the first step for the application of fingerprinting-type localization algorithms of wireless LAN devices. This paper shows how the environment for RSSI measurement is built and what network configurations yield the most reliable measurements. In the first phase of building a test-bed, configurations of off-the-shelf-equipment and the corresponding applications are explained. The second phase is to measure the RSSI in different propagation and physical environments. In this phase, different environments that have already been built in the first phase are examined. The signal strength is the only information we get from the APs that is usable for the localization process. An 'RF sensor' network can monitor RSS values on links in the network and perform device-free localization, i.e., locating a person or object moving in the area in which the network is deployed. Experimental tests reported here and in past literature are shown to validate the analysis. Â© 2015 IEEE.